Prevalence and determinants of caesarean section in a rural tertiary teaching hospital: a 6-year retrospective study - Reddy, Ke Manga; P., Lakshmi Sailaja; Kodimala, Shiva Charana; Pathakamudi, Poojitha; Betha, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Caesarean section is the most commonly performed surgery in obstetrics and there is a rise in caesarean section rates in recent times. This study was undertaken to know the changing trends in caesarean section rate in a rural hospital and to examine the indications contributing to it. The objective of the present study was to know the prevalence and changing trends in caesarean section over the last 6 years (April 2012-March 2018). Methods: Demographic data for all the deliveries, mode of delivery and indications of caesarean sections performed from April 2012 to March 2018 that occurred at MIMS were collected in a retrospective manner. Results: Among a total of 12,522 women delivered during the study period of 6 years, 44.93%, 48.49%, 48.41%, 50.9%, 45.48% and 49.62% were delivered by caesarean section during 2012-2013, 2013-2014, 2014-2015, 2015-2016, 2016-2017 and 2017-2018 respectively. Increase in repeat caesarean section is the primary reason for these increased rates followed by fetal distress. There is a rise in the repeat caesarean section from 44.36% in 2012-2013 to 55.67% in 2016-2017 and 47% in 2017-2018. Whereas primary caesarean section rate reduced from 55.63% in 2012-2013 to 44.32% in 2016-2017 and 53% in 2017-2018. Conclusions: As repeat caesarean section and fetal distress are the most common causes of caesarean section we need to address these to bring down the caesarean section rate.